Simulasi Aliran Kolom Absorpsi untuk Proses Penyerapan CO2 dengan Absorben Air menggunakan Computational Fluid Dynamics (CFD) - Novi Sylvia; Anisa Anisa; Lukman Hakim (Jurnal Teknologi Kimia Unimal, 2019)
To increasing the heating value of biogas and natural gas on  industry needed a way to separate the carbon dioxide (CO2) use technology absorption. Many methods have been used to absorb the CO2 that has been researched, but most still use the absorption process in batch system. Therefore, this research will be conducted on the process of absorption of carbon dioxide (CO2) and water (H2O) will be simulated using Computational Fluid Dynamic (CFD). This research aims to test the performance of column absorption absorption on the process of carbon dioxide (CO2) and uses Autodesk Inventor  2016 and Fluent 16.0 to model the absorption and the pressure drop on the absorption column. This research was conducted with varying influence of the flow rate of water and carbon dioxide by comparison 2:1, i.e. CO2 117.75; 141.3 ;188.4 liters/min  and  H2O 235.5; 282.6 and 376.8 liters/minute.The results obtained show that the Percent of the maximum absorption i.e. 45.89% of flow rate of CO2 occurs at 117.75 liters/minute and H2O at 235.5 litres/minute, while the percent the minimum absorption i.e. 28.32% occurred at a flow rate of CO2 188.4 liters/minute and H2O 376.8 liters/minute. The highest pressure drop occurs at 188.4 liters/minute flow rate of CO2 and H2O 376.8 liters/minute, with a value of ∆P 0.66 atm, while the lowest pressure drop occurs at 177.75 liters/minute of CO2 and H2O at 235.5 litres/minute with the value of ∆P 0.17 atm.Key words:    absorption, water, Computational Fluid Dynamic, carbon dioxide, pressure drop